TISSUE REPAIR FOR INGUINAL HERNIA: SHOULD THEY BE DELETED FROM LITERATURE? Repair for Inguinal Hernia - Sheikh, Irfan Ali; Hanif, Muhammad Shoaib; Butt, Muhammad Qasim; Shah, Shahzad Saleem (Pakistan Armed Forces Medical Journal, 2007)
Aim: This is a pilot study to evaluate the status of herniorrhaphy procedures in the modern day surgery.Duration: Mar 1995 to Mar 2005Settings: Military hospitalsType of Study: Descriptive and AnalyticalPatients and Methods: All entitled patients were included in this study and only those non-entitled patients were included who came for regular follow up. All the patients were booked at first admission and their record was maintained. They were subjected to herniorrhaphy by a modified Bassini’s procedure. They were called for follow up at 3 months, 6 months then annually for 2 years.Results: A total of 210 patients were operated for inguinal hernia by tissue repair over the period of study. Out of these 164 patients were operated by pure tissue repair, of which 148 were followed up completely and were included in the study. The average age was 50.16 + 19.12 years. The mean operation time was 20 + 5.84 minutes. Mean Hospital stay was 3 + 0.6 days. Recurrence was noted in 1 (0.68%) patient in a follow up period of 2 + 0.46 years.Conclusion: Tissue repairs hold good even today in the deserving patients and should be undertaken without hesitation where necessary. We should not hesitate in deciding for easier and cheaper alternatives when available.